Deskripsi Pemahaman Konsep Matematika Siswa Ditinjau dari Intensitas Penggunaan E-Learning Quipper Video - Fitrahlaelah Muh. Asri; Ruslan; Asdar (Issues in Mathematics Education (IMED), 2019)
This research aims to describe students’ mathematics conceptual understanding understanding with topics exponential considered of the intensity of using quipper video. This type of research is descriptive qualitative. Subjects in this study were randomly selected one for the category of high intensity, one medium intensity, and one low intensity. The data collection techniques by giving intensity questionnaires use quipper video, understanding concept tests, and interviews then through three stages of data analysis, namely data condensation, data presentation, and conclusion. The results showed that understanding mathematical concepts: (1) Subjects with high intensity of using quipper video were unable to understand the concept in indicators apply concepts or algorithms to problem solving. (2) Subjects with medium intensity of using quipper video are able to restate the concept, classify objects according to certain characteristics in accordance with the concept, use and utilize certain procedures or operations, apply concepts or algorithms to problem solving, provide examples and not examples, present concepts in various mathematical representations, and develop necessary requirements or sufficient requirements from a concept.(3) subject with low intensity of using quipper video did not understand the concept in indicator restating the concept, , provide examples and not examples,and develop necessary requirements or sufficient requirements from a concept.